Horizontal rights: an institutional approach - Bhatia, G (2021)
This Thesis develops and defends an approach to horizontal rights application, called the ‘institutional approach’. The institutional approach argues that constitutional rights ought to be applied between private parties, in situations where: (a) there exists an ‘institution’ (social, economic, or cultural), characterised by its pervasiveness and difficulty of exit (e.g., the labour market, or the family); (b) the institution creates and sustains a difference of power between the private parties; and (c) this difference in power enables one of the parties to violate the rights of the other. The Thesis is divided into two parts. Part One (Chapters One to Five) develops the theoretical and conceptual articulation of the institutional approach. Part Two (Chapters Six and Seven) applies it to two concrete legal issues, which exist across jurisdictions: the legal regulation of platform work, and of domestic relationships. The Concluding Chapter (Chapter Eight) explores the prospects of the institutional approach in contemporary constitutional adjudication.